Integration and Continuity in the Formation of Critical Thinking in Primary Class Students - Kuchkinov Abdumalik Yuldashovich; Astanakulova Nasiba Uralovna (International Journal on Integrated Education, 2022)
In the article, the subject-emotional cognitive skills, independence and activity of primary school students in the formation of critical thinking, the content of the educational process aimed at the development of critical thinking, the consideration of pedagogical-psychological integrity and continuity in the formation of critical thinking in students are discussed in the article. It is said that it should become a task that teachers constantly pay attention to.